2022
DOI: 10.1111/evj.13866
|View full text |Cite
|
Sign up to set email alerts
|

Clodronate detection and effects on markers of bone resorption are prolonged following a single administration to horses

Abstract: Background: Clodronate is a potent antiresorptive agent labelled for use in horses over 4 years of age, for the treatment of navicular syndrome. Concerns regarding the extra-label use of clodronate in equine athletes, such as racehorses, have been raised as inhibition of osteoclast activity by clodronate has been postulated to interfere with normal bone healing, which is imperative to the repair of microfractures. The paucity of data describing the long-term pharmacokinetics of clodronate and effects on biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Horses were exercised through a combination of work on a high‐speed treadmill (Mustang 2200, Graber AG, Switzerland) and exercise on an Equineciser (Centaur Horse Walkers Inc, Mira Loma, CA) prior to and throughout the course of the study (apart from the day of drug administration). Horses were exercised 5 days per week according to standard laboratory protocols 14 . As part of the laboratory protocol, all horses are subject to regular fitness testing, including weekly heart rate measurements and calculation of V 200 (running velocity that elicits a heart rate of 200 bpm) and monthly measurements of end‐run plasma lactate concentrations, as a means by which to assess the fitness level of the horses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Horses were exercised through a combination of work on a high‐speed treadmill (Mustang 2200, Graber AG, Switzerland) and exercise on an Equineciser (Centaur Horse Walkers Inc, Mira Loma, CA) prior to and throughout the course of the study (apart from the day of drug administration). Horses were exercised 5 days per week according to standard laboratory protocols 14 . As part of the laboratory protocol, all horses are subject to regular fitness testing, including weekly heart rate measurements and calculation of V 200 (running velocity that elicits a heart rate of 200 bpm) and monthly measurements of end‐run plasma lactate concentrations, as a means by which to assess the fitness level of the horses.…”
Section: Methodsmentioning
confidence: 99%
“…Horses were exercised 5 days per week according to standard laboratory protocols. 14 As part of the laboratory protocol, all horses are subject to regular fitness testing, including weekly heart rate measurements and calculation of V 200 (running velocity that elicits a heart rate of 200 bpm) and monthly measurements of endrun plasma lactate concentrations, as a means by which to assess the fitness level of the horses. Horses received grass hay in the morning and alfalfa hay at night and were supplemented with grain and stable mix in the evening.…”
Section: In Vivo Pharmacokinetic Study Animalsmentioning
confidence: 99%
“…This study follows a recently published pharmacological project on clodronate (Knych, Finno, et al, 2022). Eleven healthy who was blinded to the treatments being administered, using the American Association of Equine Practitioners scoring system (Adams, 2002;Anon, 1999).…”
Section: Horses and Exercise Trainingmentioning
confidence: 99%
“…However, efforts to enforce this ban have been difficult because there is no reliable test to determine long‐term use of bisphosphonates due to its relatively short detection window in the blood compared with its extended residence and effective time in bone (Krueger et al., 2020). A recent comprehensive study on clodronate showed that the drug is detectable up to 175 days in blood and urine by sensitive liquid chromatography–tandem mass spectrometry (LC/MS–MS), but detection in some horses was variable and inconsistent (Knych, Finno, et al., 2022). Clodronate has even been detected in bone from a horse 18 months post‐dose, suggesting that its period of effect can be extensive (Knych, Janes, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…All horses were part of the research herd at the University of California-Davis and were exercised 5 days a week, following standard protocols established by our laboratory. 9 Horses did not receive any medications for a minimum of 4 weeks before the start of the study. Before beginning the study, a complete blood count (CBC), serum biochemistry panel, and physical exam were performed, and all horses were deemed healthy.…”
Section: Animalsmentioning
confidence: 99%